Kompetensi Pedagogik Guru di Pondok Modern Darul Arqom Patean - Ahmad Ahmad; Bahruddin Bahruddin; Abdul Khalim (Cakrawala Repositori IMWI, 2023)
The Darul Arqom Patean Modern Islamic Boarding School is one of the Islamic boarding schools in Indonesia which has the principle of providing the best education so that it can form graduates or alumni who are in line with National education goals as stated in Law No. 20 of 2003 concerning the National Education System. To achieve this goal, of course, requires the role of the teacher to carry out his duties and functions in providing the best education or learning. To form quality teachers, every teacher at the Darul Arqom Patean Islamic Boarding School must fulfill their competencies as teachers, one of which is pedagogic competence. The purpose of this study was to determine the achievement of the pedagogical competency components of teachers at the Modern Darul Arqom Patean Islamic Boarding School. The research method used is descriptive qualitative with data collection methods through interviews, observation, and FGD. The number of respondents in this study was 33 consisting of pesantren leaders, heads of student care bureaus, directors of KMI, and 30 teachers. After the data was collected, data analysis was carried out so that the results of the study revealed that 9 components of pedagogic competence had been mastered by teachers so that they were in the good category, 1 component was in the sufficient category, namely the competence to guide students by being role models, and two competencies that were still in the less category, namely the first competency in mastering learning theory and learning, both understanding the characteristics of students.